Anak Budaya Ketiga POV Orang tua Indonesia - Gelda Anggraini Surya; Mary Philia Elisabeth (Dinasti Research, 2025)
Currently, the cycle of transformation of foreign culture into local culture is very rapid, rapid and seamless, especially in Indonesia. The factor causing this development is globalization. Globalization is the process of opening up foreign cultures that can be seen easily by all corners of the world. The research focus is intended to limit qualitative studies, as well as limit research to select relevant data and irrelevant data. This research focuses on the experience of raising third culture children, namely in a family consisting of a father, mother, daughter and son who are Indonesian citizens living abroad, specifically in Philadelphia. Utilization of Education While Living in Philadelphia. During the Covid-19 pandemic, there were several services provided by Public Schools in Philadelphia that were better compared to those in Indonesia. In Philadelphia there were no demonstrations by parents during the pandemic because the schools were free. During the pandemic, Public Schools in Philadelphia students were loaned notebooks from the school, in all districts each student was loaned one laptop. The internet that is needed for online learning from school is also provided if you wish, but because they already have WiFi, there is no need for this transfer. So all the homework is put on the laptop because the learning system is all online.